Socialt nedbrytande beteende eller symptom på autism? En kritisk studie av hur normer kring neuropsykiatrisk funktion påverkar domstolarnas bedömning av ”socialt nedbrytande beteende” som symtom på autism enligt LVU 3§ - Cherp,Aili (2022)
The essay aims to problematize the view of autism in Sweden's law of compulsory care. According to The Care of Young Persons Act (LVU) 3§, young people can be forced into custody for “socially destructive behavior,” which refers to the destruction of fundamental social norms. An exception to this is if the behavior is a “symptom of a mental disorder,” including autism. The essay looks at judgments from the lower Administrative courts regarding what is a symptom of autism. The rulings are analyzed from critical disability theory, which views norms around function from societal power relations. The essay does not analyze if forced custody is suitable for forced custody. It is also not an empirical study of court cases. Autism is a neurological variation and can lead to differences in social expressions, inflexibility, rigidity in movement patterns, and sensory sensitivities. According to critical disability theory, disability is formed through dichotomies about who is “normally functioning” and, on the contrary, who is not. In the same way, autism is also shaped, not only through common neurology but also through common relations to material and social reality, where autistic people are clearly distinguished from those with “normal” neurology and are marginalized when they do not act in a wanted way. This special impacts those already marginalized on other grounds, such as gender and racialization. The responsibility to adjust is put on the individual, rather than on society, to accommodate för different (neurological) functions. The court rulings show some of these norms around autism, where autistic behavior is separated from neurotypical behavior through different wordings; for example, the behavior is not a symptom of autism since it also occurs among neurotypical people. In other cases, autistic people are separated from each other, depending on the “degree” of autism that they are seen to have. This can be problematic since it risks missing internal struggles and lead to categorical rather than individual assessments. The courts often interpret symptoms of autism narrowly, which among other things, leads to an overlook of gender differences. In many cases, this language and the rulings lead to the conclusion that the behavior is not seen as a symptom of autism, making forced custody possible.
Keywords: Socialrätt; LVU 3§; socialt nedbrytande beteende; psykisk störning; tvångsvård; neuropsykiatrisk; funktionsnedsättning; NPF; autism; ADHD; kritisk metod; kritiskt funktionalitetsteori Social and welfare law; socially destructive behavior; mental disorder; forced custody; neuropsychiatric disorder; critical method; critical disorder theory